2020
DOI: 10.1021/acscatal.9b05096
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Control by Surface Graphene Oxide for Selective CO Production from Electrochemical CO2 Reduction

Abstract: Electrochemical CO 2 reduction is always accompanied by a competitive hydrogen evolution reaction as water is used as a hydrogen source. In addition to intrinsic activity control, geometrical factors of electrocatalysts such as their porous structure have been demonstrated to affect the reaction selectivity, but understanding its origin is still important. Herein, we demonstrate that reduced graphene oxide layers can effectively control the Faradaic efficiency for CO production of porous zinc nanoparticle elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…The type of catalyst material plays an important role in determining catalytic properties, elementary steps, and the overall mechanism and pathway of the reaction. Earlier mechanistic studies have focused on obtaining key catalytic parameters related to performance, total yield, selectivity, and Faradaic efficiency under hard assumptions such as absence of mass transport limitation, low intermediate coverage and steady-state reaction conditions [260,262,263].…”
Section: Modeling Electrochemical Co 2 Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The type of catalyst material plays an important role in determining catalytic properties, elementary steps, and the overall mechanism and pathway of the reaction. Earlier mechanistic studies have focused on obtaining key catalytic parameters related to performance, total yield, selectivity, and Faradaic efficiency under hard assumptions such as absence of mass transport limitation, low intermediate coverage and steady-state reaction conditions [260,262,263].…”
Section: Modeling Electrochemical Co 2 Reductionmentioning
confidence: 99%
“…Three-dimensional (3D) porous electrodes have also been used for CO 2 RR, where the porosity of the catalytic medium provides an additional parameter to tune concentration gradients of active species and thereby control the selectivity [255,262]. Experimental studies have shown that the selectivity of CO 2 RR can be considerably improved by increasing electrode porosity.…”
Section: Product Selectivitymentioning
confidence: 99%
See 3 more Smart Citations